Radicalization in the Social Media Era: Understanding the Relationship between Self-Radicalization and the Internet - Hollewell, Georgia F. (International journal of offender therapy and comparative criminology, 2022)
September 11th was a turning point in the understanding of terrorism and radicalization. The Internet has provided an instrumental change regarding how terrorists communicate and spread their propaganda, proving a cause of concern for counterterrorism units. The increased use of social networking platforms has provided a significant change in the process of self-radicalization, with younger generations at greater risk. The aim of the project was to study the relationship between social media and self-radicalization among college and university students. A sample of 499 participants was recruited throughout Amazon Mechanical Turk and social media platforms. Measures on emotional intelligence, psychological involvement on social media, attitudes toward terrorism, and political violence, and loneliness were gathered. Results showed that individuals holding a university degree—especially young men—were more at risk of endorzing positive attitudes toward political violence and terrorism, and, therefore, more at risk of being radicalized.